Reformasi Birokrasi Lokal (Studi Kasus di Sekretariat Daerah Kabupaten Timor Tengah Selatan) = Reformation of Local Bureaucracy (A Case Study at the Regional Secretariat of the South Central TimorRegency) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The principles of modern bureaucracy are basically identical to those of the modern management. Some of the principles are having the ability to have professional, learning process